The Pine Branch, February 1929 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1929)
The Pine Branch, February 1929. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia, 1929 Includes: editorials, photographs, poems, short stories, and other writings.
After Twilight: Hasel Donahue 3| Rain: M K Burrows 4| "Pity Melts the Mind to Love"?: Hasel Donahue 8| Lilith to Eve: Hasel Donahue 8| Courage Mounts with Occasion: Caroline Parrish 9| "That's My Weakness Now"?: Lucile C Nix 13| Two Songs for a Matron: Hasel Donahue 18| The Extra Plate: Dorothy Harper 19| Editorial 23| Y W C A News 24| Athletic News 25| Society News 26| Alumnae News 27| Locals 29| Jokes 31
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education